Level of mental Imagery among the players of the Syrian national wrestling team " Men's Category " - كفا, عزيز; ماضي, أنجيلا (Latakia University Journal -Medical Sciences Series, 2023)
The aim of this research is to identify the level of mental imagery of the players of the national wrestling team "men's category", in addition to identifying the differences in the level of this imagery according to participation or not in foreign tournaments, and according to the type of wrestling practiced, whether free or Romanian. The mental perception scale designed by (Martiz, 1993), and its Arabic image (Rateb, 2007), were distributed to a sample consisting of (14) players from the national wrestling team "men's category", for the training season (2021-2022). The results of the study indicated that the level of mental perception among the players of the national wrestling team "men's category" was high, and these results did not show any differences between the players of the national wrestling team who participated in external and internal championships. In addition, there were no differences in the level of mental imagery between the players of the national team for freestyle wrestling compared to the players of the national team for Romanian wrestling.